2017
DOI: 10.3892/ol.2017.5692
|View full text |Cite
|
Sign up to set email alerts
|

miR-215 suppresses proliferation and migration of non-small cell lung cancer cells

Abstract: The expression of microRNA-215 (miR-215) in non-small cell lung cancer (NSCLC) tissues and the effects of miR-215 on the proliferation and migration of NSCLC cells were investigated. qRT-PCR was used to detect the expression of miR-215 in NSCLC tissues and paired normal tumor-adjacent lung tissues; MTT assay, transwell assay and soft-agar assay were used in vitro to evaluate the role of miR-215 on proliferation, migration and cell clonality on NSCLC cells, after transfecting miR-215 mimics to NSCLC cell line A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Therefore, new prognostic markers and treatment options are urgent for the improvement of medical treatment for patients with breast cancer. Previous investigations have determined that miR‐215 serves as an anti‐oncogene in several kinds of cancers, but the mechanisms by which miR‐215‐5p is involved in breast carcinoma progression have not been effectively studied . This current study reveals that miR‐215‐5p is down‐regulated in breast cancer and is negatively correlated with the progression and metastasis of breast carcinoma.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, new prognostic markers and treatment options are urgent for the improvement of medical treatment for patients with breast cancer. Previous investigations have determined that miR‐215 serves as an anti‐oncogene in several kinds of cancers, but the mechanisms by which miR‐215‐5p is involved in breast carcinoma progression have not been effectively studied . This current study reveals that miR‐215‐5p is down‐regulated in breast cancer and is negatively correlated with the progression and metastasis of breast carcinoma.…”
Section: Discussionmentioning
confidence: 66%
“…36 miR-215 exhibited not only tumor suppression but also tumor promotion function in some cancer types such as non-small cell lung cancer, gastric cancer and glioma, which indicated its dual function in cancer development. [37][38][39][40][41] For miR-146-5p, a member of miR-16 family, it was supposed to be a tumor suppressor for various cancers, [42][43][44] but little was known about its role in BC. On the contrary, miR-210 could be a tumor promoter, which was reported to be associated with poor prognosis for BC patients via different biological pathways such as hypoxia induction, invasive transformation and tumor proliferation promotion.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA-215-5p Prominently Suppressed HG-Induced MPC5 Cell Migration. It has been demonstrated that miRNA-215 was a negative regulator for cell migration and invasion in many diseases [23][24][25]. When the expression of miRNA-215-5p using mimics in MPC5 cells was forced, its decline was recovered in the presence of HG (Figure 3(a)).…”
Section: The Mir-215-5pmentioning
confidence: 98%